Budaya Organisasi Memoderasi Pengaruh Adopsi SIA pada Kinerja Organisasi - Yurinne Wahyudi, Julia; Ariyanto, Dodik (E-Jurnal Akuntansi, 2020)
The study aims to determine the effect of information quality, service quality, system quality on organizational performance with organizational culture as a moderating variable. The research population is starred hotel employees in Badung Regency who use technology-based accounting information systems, especially the accounting and front office departments. The data collection technique used is saturated samples. Sampling obtained research samples of 90 star hotel employees in Badung Regency. The data analysis technique used is moderated regression analysis. The results showed that information quality, service quality, system quality had an effect on organizational performance. Organizational culture can strengthen the influence of information quality, service quality, system quality on organizational performance. It can be concluded that the adoption of technology that is proxied by organizational performance is influenced by the quality of information, service quality, system quality, especially accounting information systems in hotels. Keywords: Accounting Information System; Organizational Performance; Organizational Culture.